1998
DOI: 10.1159/000029827
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Enzymes: Their Role in Homeostasis and Their Relationships with Dermatoses

Abstract: This review underlines the importance of different enzymes (β-glucocerebrosidase, phospholipase A2, proteases and cholesterol sulfatase) in the formation and maintenance of the epidermal barrier function. Certain diseases may be characterized by the lack or excess of one or more of these different enzyme activities, altering the homeostatic equilibrium of the epidermis. In addition to this, particular enzymes may show potential in the development of novel dermocosmetic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…These hydrolases include ␤ -glucocerebrosidase, acid sphingomyelinase, acid lipases, phosphatases and phospholipases [9] . ␤ -Glucocerebrosidase with an optimum pH of 5.6 is involved in the synthesis of the most important ceramides.…”
Section: Barrier Functionmentioning
confidence: 99%
“…These hydrolases include ␤ -glucocerebrosidase, acid sphingomyelinase, acid lipases, phosphatases and phospholipases [9] . ␤ -Glucocerebrosidase with an optimum pH of 5.6 is involved in the synthesis of the most important ceramides.…”
Section: Barrier Functionmentioning
confidence: 99%
“…These lipids form the lamellar structure and provide an intercellular lipid barrier. The protein expression and activation involved in SC formation require high calcium (Ca 2+ ) levels or an acidic pH [11,12]. Therefore, for cornification, it is important to maintain the intracellular and extracellular environment from the upper SG to lower SC.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies [3][4] we described and analyzed the enzymes involved in generating this protective envelope and showed that in dry, non-eczematous atopic dermatitis, the phosphatase-like and trypsin-like activities are altered. The present study pursues these investigations in the same type of pathology but in cases involving an inflammatory component.…”
Section: Introductionmentioning
confidence: 99%